A SOCIO-ECONOMIC CHARACTERIZATION OF A SMALL SCALE MORMYRID BASED BAIT FISHERY IN THE KAINJI LAKE BASIN - OLAOSEBIKAN, B.D.; OGUNLEYE, A. (Nigerian Journal of Fisheries, 2014)
Small-scale artisanal fisheries that target baitfish have been largely unnoticed and little is known about this fishery in Africa, despite their great importance in the fisheries of many inland water bodies in Africa. This study assessed a bait fishery in the Niger basin in Nigeria based on a small mormyrid, Pollimyrus petricolus (Daget, 1954). The socioeconomic characteristics of the stakeholders, bait-fishers, wholesalers, retailers and bait-users were described based on personal interviews. Most of the stakeholders are above 40 years of age (76.8%) with an average years of experience of 24.2 years in the bait fishery. The fishery is seasonal from November to June and is conducted mainly in the upper reaches of Lake Kainji floodplain while the baitfish is sold and utilized throughout Kainji and Jebba Lakes basin. Four different gears are used for the collection of baitfishes, Malian trap, Cast-net, Dip-net and Double Chambered non-return valve trap (Ndurutu), however the most preferred gears are Malian and Cast-net. Daily catch range from 500-2000 fish per fisher with December to February being the peak fishing period. The baitfish is usually transported in 50 litre jerrican covered with sack. Prices of bait fish were found to fluctuate with season. Analysis of marketing margin shows a market margin of 98,100 per week and marketing efficiency of 1.29. Fish caught with Pollimyrus bait are mainly Lates niloticus, Bagrus species, Heterobranchus species, Synodontis species and Hydrocynus species. The strength of the stakeholders includes high demand for live baitfish in the Kainji and Jebba Lakes’ fisheries and availability of P. petricolus in large quantity while the main weakness is the seasonal availability of the baitfish. Over-exploitation and pollution from agricultural activities in the catchment of the P. petricolus fishing ground are the threats identified by the stakeholders.